LAKOFF, Andrew (2005), Pharmaceutical Reason: Knowledge and Value in Global Psychiatry - Ablard, Jonathan (Centro de Estudios Avanzados, 2012)
LAKOFF, Andrew (2005), Pharmaceutical Reason:Knowledge and Value in Global Psychiatry. Cambridge:Cambridge University Press, 206 páginas.